2013
DOI: 10.7860/jcdr/2013/5862.3344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ‘Water Induced Thermogenesis’ on Body Weight, Body Mass Index and Body Composition of Overweight Subjects

Abstract: The decrease in body weight, body mass index and body composition scores of overweight subjects at the end of study period establishes the role of water induced thermogenesis in weight reduction of overweight subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Multiple studies have shown that CB consumption is strongly associated with weight gain, type 2 diabetes mellitus and cardiovascular diseases [ 5 - 9 ]. On the other hand, the intake of PW does not have any adverse effects on people’s health, improves hydration [ 10 ], increases satiety [ 11 ] and thermogenesis [ 12 ], contributes to a minor energy intake of a total diet [ 13 ] and it has been observed that facilitates weight loss [ 10 , 11 ]. Despite these benefits, the evidence of the causal relation between intake of PW and weight loss is not convincing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that CB consumption is strongly associated with weight gain, type 2 diabetes mellitus and cardiovascular diseases [ 5 - 9 ]. On the other hand, the intake of PW does not have any adverse effects on people’s health, improves hydration [ 10 ], increases satiety [ 11 ] and thermogenesis [ 12 ], contributes to a minor energy intake of a total diet [ 13 ] and it has been observed that facilitates weight loss [ 10 , 11 ]. Despite these benefits, the evidence of the causal relation between intake of PW and weight loss is not convincing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study revealed that drinking excessive warm water over and above daily intake as per Japan water therapy, and then, considerable weight loss among subjects can be seen; this can be due to the effect of warm water that helps in increasing metabolic rate that will promote burning calories quickly. A similar study was done on overweight girls to see the effect of water-induced thermogenesis and suggested that there was a decrease in body weight, BMI, and body composition scores which were seen in overweight subjects who establish the role of waterinduced thermogenesis that is helping in increasing the metabolic rate in weight reduction of overweight subjects [13].…”
Section: Discussionmentioning
confidence: 84%
“…However, the mechanism remains unclear. Some studies have suggested that water intake elicited acute changes in human physiology because it provides a sympathetic stimulus, increasing the metabolic rate, which in turn augments the daily energy expenditure (28,29). Other authors reported that water drinking activates the autonomic nervous system and induces acute hemodynamic changes (30).…”
Section: Discussionmentioning
confidence: 99%